Testing of multiple samples increases the sensitivity of stool decay-accelerating factor test for the detection of colorectal cancer - Mizuno, Masakatsu; Mizuno, Motowo; Iwagaki, Naofumi; Nasu, Junichirou; Okazaki, Hiroaki; Yamamoto, Kazuhide; Okada, Hiroyuki; Tsuji, Takao; Fujita, Teizo; Shiratori, Yasushi (Am J Gastroenterol, 2003)
We previously reported that the measurements of stool decay-accelerating factor (DAF), a membrane-bound, complement regulatory protein, may be valuable for the detection of colorectal cancer. Recently we have refined the immunoassay for stool DAF. In the present study, using the refined assay, we measured stool DAF concentrations in multiple samples from patients with colorectal cancer and in healthy controls to determine whether testing of multiple samples would increase the sensitivity of the stool DAF test. DAF was measured in three spontaneously passed stool samples from each of 100 patients with colorectal cancer and 100 control subjects without apparent colorectal disease. The stool DAF concentrations in the patients with colorectal cancer (median 11.1 ng/g stool; interquartile range 2.9–32.7 ng/g) were significantly higher than concentrations in the subjects without colorectal diseases (median 1.6 ng/g stool; interquartile range 0.4–3.4 ng/g) (p < 0.0001). Testing of two samples from each patient significantly increased the sensitivity (72%) of the stool DAF test without significantly decreasing its specificity (92%). The stool DAF test was positive in more than one half of patients with colorectal cancer at a relatively early TNM stage or with negative fecal occult blood test. These findings suggest that stool DAF is a marker of colorectal cancer independent of fecal occult blood and testing of two samples increases the sensitivity of the stool DAF test. Measurement of stool DAF now seems worthy of further consideration as a noninvasive method for the detection of colorectal cancer.